Locating hell in islamic traditions - Lange, Christian Robert (Islamic history and civilization, 2016)
Islam is often seen as a religious tradition in which hell does not play a particularly prominent role. This volume challenges this hackneyed view.This book is the first book-length analytic study of the Muslim hell. It maps out a broad spectrum of Islamic attitudes toward hell, from the Quranic vision(s) of hell to the pious cultivation of the fear of the afterlife, theological speculations, metaphorical and psychological understandings, and the modern transformations of hell...